Análise computacional da interação entre o canal de sódio NaV1.7 humano e diferentes monoterpenoides - Fernandes, Alana Lígia Saldanha (2022)
Human NaV1.7 is one of the 9 functional isoforms of voltage-gated sodium channels, they are transmembrane proteins, mainly expressed in cells of the peripheral nervous system, being closely related to the perception and transmission of pain. Some mutations can affect these proteins, triggering their malfunction and causing channelopathies, which are currently treated by means of modulators with broad and nonspecific action, generating side effects. Aiming at this problem, the work investigated the modulation of human subtype 1.7 sodium channels by four monoterpenoids commonly found in essential oils of plant species common in northeastern Brazil (anethole, estragole, eugenol and linalool) based on studies of the same nature. and the like already developed with these molecules. The work started with the detection of possible interaction sites using the DoGSiteScore tool and with broad prospecting through molecular docking; the results, nine possible sites of interaction, were evaluated in detail by specific molecular docking calculations. Of the six interaction sites considered based on binding energy and interaction patterns, 4 of them had already been described in the literature. The one for local anesthetics which is located inside the central pore; the site of the toxins, determined by the residues that make up the selectivity filter and its neighbors; the third and fourth sites are concentrated in voltage sensing domains 2 and 4, respectively, characterized by interaction with at least one of the blocking/activation loads; the fifth site is located in a cytosolic region and the sixth site is in a VSD-PM contact region that suggests, by location, a possible interference in the PM opening/closing. The minimization of protein-ligand complexes showed few significant differences in the pattern of interaction displayed in the docking calculations and the data of the energetic contributions highlighted the main residues that acted in the anchoring of the ligands. Therefore, based on the structural results and relating them to data obtained from some experiments that evaluated the action of these molecules on excitability and nerve conduction, it is concluded that these monoterpenoids can be used for the modulation of NaV1.7, although issues such as the best dosage or form of application require specific studies to reach their potential.